Efficient bioremediation of crude oil contaminated soil by a consortium of in-situ biosurfactant producing hydrocarbon-degraders - Saman Hosseini; Rouhallah Sharifi; Alireza Habibi (Scientific Reports)
Abstract Soil contamination by crude oil is a common occurrence during accidental spills, transportation, or refining processes. Bioremediation as an environmentally friendly and cost-effective approach is interesting for treating hydrocarbon-contaminated sites via natural microorganisms to break down or transform the hydrocarbons into less toxic substances. However, the bioremediation process is time-consuming due to the low accessibility of cells to hydrocarbon contaminants in soil. Applying hydrocarbon degraders with the capability to produce biosurfactants during the hydrocarbon degradation pathways could significantly handle the problem. In this study, a bacterial consortium consists Roseomonas aestuarii, Pseudomonas oryzihabitans, Pantoea agglomerans, and Arthrobacter sp. was evaluated for crude oil removal from the aqueous environment and soil microcosm. To examine the effect of supplementary biosurfactants in the bioremediation process, surfactin and rhamnolipid (ratio 1:1) were used at a concentration of 1000 ppm. Our findings indicate the consortium has high potential in removing saturated hydrocarbons from aqueous (removal yield = 96.16% after 9 days) and soil (removal yield = 64.65% after 120 days) environments. The consortium had a significantly higher removal efficiency than the single-cell treatments, possibly due to the species’ synergistic effect. The GC-MS analysis confirmed a uniform removal of different molecular weight hydrocarbons by the consortium from soil. However, adding supplementary biosurfactants showed a slight modification in the consortium’s performance after 120 days in soil microcosms (removal yield for saturated hydrocarbons was 65.97%). This study showed the potential application of this in-situ producing biosurfactant consortium for bioremediation purposes.